On constructive description of Gibbs measures for the Potts model on a Cayley tree - Rahmatullaev, M.; Rafikov , F. К.; Azamov , Sh. Kh. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.9We consider the Potts model on a Cayley tree and prove the existence of Gibbs measures built by using the method suggested in [H. Akin, U. A. Rozikov, S. Temir, A new set of limiting Gibbs measures for the Ising model on a Cayley tree, J. Stat. Phys., 142, № 2, 314 – 321 (2011)]. In addition, we prove that there exist $(k_0)$-translation invariant Gibbs measures for the Potts model on a Cayley tree and calculate the free energy of these Gibbs measures.